Digital Economy and Social Capital on the Example of Selected EU Countries - Michal GOLINSKI (Communications of International Proceedings, 2020)
A new civilization revolution – commonly referred to as digital - is unfolding before our eyes. The changes it entails will affect the society, economy, culture and politics - virtually all areas of our reality. The world that is being created will be subject to constant change. An analysis of the relationship between digitalization processes and social capital in EU countries, with special attention to Central and Eastern Europe (CEE), is the objective of this paper. Its results reveal a low level of social capital (SC) in the countries of this region, which constitutes a development barrier that may exclude CEE countries from fully benefiting from civilization transformations and catch them in the middle-income trap.
Keywords: Information Economy; Digital Economy; Digital Multiverse; Social Capital; Online Social Capital; E-Metrics.